Barriers and facilitators to accessing skilled birth attendants in Afar region, Ethiopia. Issue 5 (May 2015) - King, Rosemary; Jackson, Ruth; Dietsch, Elaine; Hailemariam, Asseffa
Abstract Objective to explore barriers and facilitators that enable women to access skilled birth attendance in Afar Region, Ethiopia. Design researchers used a Key Informant Research approach (KIR), whereby Health Extension Workers participated in an intensive training workshop and conducted interviews with Afar women in their communities. Data was also collected from health-care workers through questionnaires, interviews and focus groups. Participants fourteen health extension workers were key informants and interviewers; 33 women and eight other health-care workers with a range of experience in caring for Afar childbearing women provided data as individuals and in focus groups. Findings participants identified friendly service, female skilled birth attendants (SBA) and the introduction of the ambulance service as facilitators to SBA. There are many barriers to accessing SBA, including women׳s low status and restricted opportunities for decision making, lack of confidence in health-care facilities, long distances, cost, domestic workload, and traditional practices which include a preference for birthing at home with a traditional birth attendant. Key conclusions many Afar men and women expressed a lack of confidence in the services provided at health-care facilities which impacts on skilled birth attendance utilisation. Implications for practice ambulance services that are free of charge to women are effective as a means to transfer women to a hospital for emergency care if required and expansion of ambulance services would be a powerful facilitator to increasing institutional birth. Skilled birth attendants working in institutions need to ensure their practice is culturally, physically and emotionally safe if more Afar women are to accept their midwifery care. Adequate equipping and staffing of institutions providing emergency obstetric and newborn care will assist in improving community perceptions of these services. Most importantly, mutual respect and collaboration between traditional birth attendants (Afar women׳s preferred caregiver), health extension workers and skilled birth attendants will help ensure timely consultation and referral and reduce delay for women if they require emergency maternity care.